A Biocatalytic One‐Pot Approach for the Preparation of Lignin Oligomers Using an Oxidase/Peroxidase Cascade Enzyme System. Issue 19 (14th September 2017) - Habib, Mohamed H. M.; Deuss, Peter J.; Lončar, Nikola; Trajkovic, Milos; Fraaije, Marco W.
Abstract: Synthetic lignin was prepared biocatalytically in a one‐pot, two‐step reaction using an oxidase/peroxidase cascade enzyme system. Using eugenol in combination with eugenol oxidase and a peroxidase, lignin‐like material was produced. The cascade reaction takes advantage of the ability of the oxidase to produce coniferyl alcohol and hydrogen peroxide from eugenol and molecular oxygen. The hydrogen peroxide is used by the peroxidase for the formation of crosslinks that typify lignin. As eugenol oxidase has a broad substrate acceptance profile, also 4‐allylphenol (chavicol) and 4‐allyl‐2, 6‐dimethoxyphenol could be used as precursors of the synthetic lignin. As a result, all three naturally occurring monolignols could be prepared and incorporated in the synthetic lignin. The reaction was optimized in order to achieve the highest possible yield of insoluble lignin oligomers and scaled up to 1 gram. Analysis of the water‐insoluble product by gel permeation chromatography revealed the formation of relatively small lignin oligomers (≈1000 dalton). By using two‐dimensional heteronuclear single quantum coherence nuclear magnetic resonance spectroscopy (2D HSQC NMR) analysis it could be demonstrated that the material contained α‐ O ‐4/β‐ O ‐4, β‐ O ‐4, β‐β, β‐5 linkages and dibenzodioxocin units. All these features indicate that the biocatalytically produced material closely resembles natural lignin. While 54% of eugenol was converted into water‐insoluble oligomers, the remaining substrate was converted into water‐soluble dimers and tetramers which are important lignin model compounds. Therefore, the presented method represents a valuable and facile biocatalytic approach for the preparation of lignin‐like material and potentially valuable chemicals. Abstract :